Ranking radiotherapy treatment plans - Ebert, Martin (Radiology and oncology (Ljubljana), 2001)
Background. The ranking of treatment plans in radiotherapy is of importance when there are alternative approaches to treating an individual patient, in assessment of dose information collected during clinical trials and in formulation of objectives for optimization routines. Methods. Several physically and radiobiologically-based dose indices were calculated for a series of model dose-volume histograms (DVHs). The ranking of these DVHs according to each dose index was examined. Variation in the ranking of the radiobiological indices with parameters used in the models was also examined. Ranking according to the indices was also examined for DVHs of planning targetvolumes (PTVs) for a series of 18 patients treated with external beam radiotherapy for prostate carcinoma. Results. It was found for both the model and real DVHs that treatment plan ranking depends explicitly on the model usedfor ranking target volume doses (i.e., the dose index used). For the radiobiological models, there is a strong dependence of DVH ranking on the radiobiological parameters used in the models (specifically, the 'alpha' valuefrom the linear-quadratic model). Conclusion. When ranking radiotherapy treatment plans during planning or in evaluation of clinical trials, attentionshould be paid to the models used in dose evaluation.
Keywords: Prostatic neoplasms; Radiobiology; radiološko zdravljenje; Radiotherapy; Radiotherapy dosage; Radiotherapy planning, computer-assisted; rak (medicina); therapy; zdravljenje